2012
DOI: 10.1021/ja301867s
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Malonic Anhydrides

Abstract: Malonic anhydrides decompose at or below room temperature, to form a ketene and carbon dioxide. Rate constants for the thermal decomposition of malonic, methylmalonic, and dimethylmalonic anhydrides were measured by NMR spectroscopy at various temperatures, and activation parameters were evaluated from the temperature dependence of the rate constants. Methylmalonic anhydride is the fastest, with the lowest ΔH(‡), and dimethylmalonic anhydride is the slowest. The nonlinear dependence on the number of methyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Recently, we returned to the kinetics of this decomposition, now that NMR instrumentation has become sensitive enough to permit concentrations low enough that the peroxide byproducts do not endanger the researcher or the spectrometer probe. We found that the enthalpy of activation is exceptionally low and that the entropy of activation is positive, consistent with a concerted [2 + 2] process that requires a more organized antarafacial transition‐state structure . We also found that the rates are not monotonic in the number of methyl substituents, and we rationalized this behavior with density‐functional theory (DFT) calculations.…”
Section: Researchmentioning
confidence: 60%
“…Recently, we returned to the kinetics of this decomposition, now that NMR instrumentation has become sensitive enough to permit concentrations low enough that the peroxide byproducts do not endanger the researcher or the spectrometer probe. We found that the enthalpy of activation is exceptionally low and that the entropy of activation is positive, consistent with a concerted [2 + 2] process that requires a more organized antarafacial transition‐state structure . We also found that the rates are not monotonic in the number of methyl substituents, and we rationalized this behavior with density‐functional theory (DFT) calculations.…”
Section: Researchmentioning
confidence: 60%
“…This has demonstrated higher amount of malonic acid was required for a more complete ring opening of epoxides to form the polyester polyol. In addition, dehydration of malonic acid in forming carbon suboxide (C 3 O 2 ) could cause some loss of malonic acid, hence resulting in requiring higher amount of malonic acid in the reaction . All the polyester polyols (PPM 1‐PPM 6) demonstrated desirably low AV of approximately 1 mg KOH/g sample.…”
Section: Resultsmentioning
confidence: 99%
“…From the kinetics, H ‡ is quite low, near 14 kcal/mol, and S ‡ is near -20 cal/mol-K, negative because this is a [2 s +2 a ] cycloreversion, via a more organized transition state. 50 Scheme 9. Synthesis and reactivity of malonic anhydrides (R = H, CH 3 ).…”
Section: Dicarboxylate Monoanionsmentioning
confidence: 99%